Relations of Changes in Serum Carcinoembryonic Antigen Levels before and after Neoadjuvant Chemoradiotherapy and after Surgery to Histologic Response and Outcomes in Patients with Locally Advanced Rectal Cancer - Saito, Gota; Sadahiro, Sotaro; Ogimi, Takashi; Miyakita, Hiroshi; Okada, Kazutake; Tanaka, Akira; Suzuki, Toshiyuki (Oncology, 2018)
Objectives: The histologic response to neoadjuvant chemoradiotherapy (nCRT) has been intimately related to outcomes in locally advanced rectal cancer. Serum carcinoembryonic antigen (CEA) levels change after nCRT and after surgery as compared with before nCRT. Methods: The subjects were 149 patients with locally advanced rectal cancer who received nCRT between 2005 and 2013. The patients were divided into 4 groups according to the serum CEA levels: group 1, 55 patients with negative serum CEA levels before nCRT; group 2, 41 patients with positive serum CEA levels before nCRT that became negative after nCRT; group 3, 37 patients with positive serum CEA levels after nCRT that became negative after surgery; and group 4, 16 patients with positive serum CEA levels after nCRT as well as after surgery. Results: Pathological complete response, T downstaging, and tumor shrinkage were significantly higher in group 1 than in other groups. Disease-free survival was significantly poorer in group 4. The lack of a decrease in the serum CEA level in group 4 was most likely attributed to the persistence of micrometastases outside the resection field. Conclusions: Changes in serum CEA levels measured before nCRT, after nCRT, and after surgery can be used to reliably predict the histologic response to nCRT and outcomes.